Pregnancy and Severe Influenza Infection in the 2013–2014 Influenza Season. Issue 1 (January 2015) - Louie, Janice K.; Salibay, Catheryn J.; Kang, Monica; Glenn-Finer, Rose E.; Murray, Erin L.; Jamieson, Denise J.
Abstract : OBJECTIVE: To describe the epidemiologic and clinical characteristics of critically ill pregnant and postpartum women with influenza infection reported in the 2013–2014 season. METHODS: The California Department of Public Health conducts surveillance for patients with laboratory-confirmed influenza who die or require hospitalization in intensive care units. For this case series, we reviewed data on pregnant and postpartum (6 weeks or less from delivery) women reported in the 2013–2014 influenza season. RESULTS: From September 29, 2013, through May 17, 2014, 17 pregnant women with severe influenza were reported. The median age was 29 years (range 17–44 years). Sixteen (94%) were in the second or third trimester. Fifteen (88%) patients were hospitalized, nine (53%) required mechanical ventilation, five (29%) required emergent cesarean delivery, and four (24%) died. Of 14 patients with available information, only two (14%) received influenza vaccination during pregnancy. Seven patients who tested positive by polymerase chain reaction also had rapid influenza diagnostic testing performed; only one (14%) had a positive rapid influenza diagnostic test results. Fifteen patients received antiviral treatment; four (27%) began treatment within 48 hours of symptom onset. One additional patient was 36 days postpartum and required intensive care unit admission and mechanical ventilation for influenza-associated acute respiratory distress syndrome. CONCLUSION: Influenza remains a significant cause of morbidity and mortality in pregnant and postpartum women; in our series, a majority were not vaccinated. During the influenza season, pregnant women with suspected influenza should receive prompt empiric antiviral therapy, regardless of rapid influenza diagnostic test results or vaccination status. LEVEL OF EVIDENCE: III Abstract : Of 18 pregnant or postpartum women with severe or fatal influenza, most were not vaccinated, and false-negative rapid influenza diagnostic test results were common.